Psychology and behavioral economics applications for public policy - Ruggeri, Kai (Abingdon, Oxon Routledge, 2022)
Psychology and Behavioral Economics offers an expert introduction to how psychology can be applied to a range of public policy areas. It examines the impact of psychological research for public policy making in economic, financial and consumer sectors, in education, healthcare and at workplace, for energy and the environment, and in communications. Your energy bills show you how much you use compared to the average in your area. Your doctor sends you a text message reminder when your appointment is coming up. Your bank gives you three choices for how much to pay off on your credit card each month. Wherever you look, there has been a rapid increase in the amount of interest we place on understanding real human behaviors in everyday decisions, and these behavioral insights are now regularly used to influence everything from how companies recruit employees through to large-scale public policy and government regulation. But what is the actual evidence behind these tactics, and how did psychology become such a major player in economics? Answering these questions and more, this team of authors working across both academia and government present this fully revised and updated reworking of Behavioral Insights for Public Policy. This update covers everything from the history of how policy was historically developed, major research in human behavior and social psychology, and key moments that brought behavioral sciences into the forefront of public policy. Featuring over 100 empirical examples of how behavioral insights are being used to address some of the most critical challenges faced globally, key topics covered include evidence-based policy, a brief history of behavioral and decision sciences, behavioral economics, and policy evaluation, all illustrated throughout with lively case studies and major empirical examples. Including end-of-chapter questions, a glossary, and key concept boxes to aid retention, as well as a new chapter revealing the work of the Canadian Government's behavioral insights unit, this is the perfect textbook for students of psychology, economics, public health, education, and organizational sciences, as well as public policy professionals looking for fresh insight into the underlying theory and practical applications in a range of public policy areas"--
TABLE OF CONTENTS: CHAPTER I: Psychology and policy / Kai Ruggeri, Kamilla Knutsen Steinnes, Maja Friedemann, and Fadi Makki - - CHAPTER II: A brief history of behavioral and decision sciences / Kai Ruggerri, Jana B. Berkessel, Philipe M. Bujold, Maja Friedemann, Hannes Jarke, Kamilla Knutsen Steinnes, Mary MacLennen, Sahana K. Quail, Felice L. Tavera, Sanne Verra, Faisal Naru, Filippo Cavassini, and Elizabeth Hardy - - CHAPTER III: An introduction to behavioral economics / Kai Ruggeri, Hannes Jarke, Maja Friedemann, Faisal Naru, and Francesca Papa - - CHAPTER IV: Economic, financial, and customer behavior / Kai Ruggeri, Maja Friedemann, Jakub M. Krawiec, Hannes Jarke, Sahana K. Quail, Alessandro F. Paul, Tomas Folke, and Enrico Rubaltelli - - CHAPTER V: Health behavior and decision-making in healthcare / Hannes Jarke, Kai Ruggeri, Joahanna Graeber, Markus R. Tunte, Olatz Ojinaga-Alfageme, Sanne Verra, Dafina Petrova, Amel Benzerga, Zorana Zupan, and Matteo M. Galizzi - -
CHAPTER VI: Energy and environmental behavior / Sara Morales Izquierdo, Manou Willems, Johanna Emilia Immonen, Amel Benzerga, Ondrej Kacha, Kai Ruggeri, and Sander van der Linden - - CHAPTER VII: Education and behavior / Carly D. Robinson, Thomas Lind Andersen, Clair Davison, Emir Demic, Hamish Evans, Mafalda Fontinha, Mascarenhas, Shannon P. Gibson, Renata Hlavova, Wing Yi Lam, Silvana Mareva, Aleksandra Yosifova, and Kai Ruggeri - - CHAPTER VIII: Work and workplace decision-making / Ralista Karakasheva, Jascha Achterberg, Jana B. Berkessel, Alessia Cottone, Julia Dhar, Jon M. Jachimowicz, Yuna S. M. Lee, Ashley Whillans, and Kai Ruggeri - - CHAPTER IX: Communication and behavioral economics / Marlene Hecht, Nejc Pohl. Bojana Veckalov, Julia P. Stuhlreyer, Kai Ruggeri, and Sander van der Linden - - CHAPTER X: Evidence-based policy / Kai Ruggeri, Olatz Ojinaga-Alfageme, Amel Benzerga, Jana B. Berkessel, Maja Friedemann, Renata Hlavova, Marvin Kunz, Nejc Plohl, Felicia Sundstrom, and Tomas Folke - - CHAPTER XI: Policy evaluation and behavioral economics / Kai Ruggeri, Julia P. Stuhlreyer, Johanna Emilia Immosen, Silvana Mareva, Maja Friedemann, Alessandro F. Paul, Matthew Lee, and Rachel C. Shelton - - CHAPTER XII: Behavioral insights - a Government of Canada perspective / Elizabeth Hardy, Haris Khan, and Meera Paleja - - CHAPTER XIII: Behavioral impacts for public policy / Kai Ruggeri.
Earlier edition published in 2019 as: Behavioral insights for public policy : concepts and cases.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Psychology, Applied; Economics -- Psychological aspects; Policy sciences -- Psychological aspects; Political planning -- Psychological aspects